Dispersive magnetic excitations in non-superconducting PrBa2Cu3O6+x (x approximate to 0.93) - Gardiner, C; Lister, S; Boothroyd, A; Andersen, N; Zhokhov, A; Stunault, A; Hiess, A (2002)
We report preliminary results of a neutron inelastic scattering study of the magnetic excitations in single-crystal PrBa2Cu3O6+x (x approximate to 0.93). The measurements probe (i) the dispersion of the low-energy crystal field levels of the Pr ion in the low-temperature AFIII magnetic phase and (ii) the Cu optic spin wave mode gap in the AFI magnetic phase. We compare the results with previous measurements made when the same crystal was in an oxygen-deficient state, and thus establish the effect of hole doping on the magnetic excitations.